Methodological instructions to calculation assignments "Thermodynamic and heat transfer processes" of the course "Theoretical Fundamentals of Heat Engineering" - Pylyov, V. V. (My University, 2023)
Principles ruling thermodynamic and heat transfer processes are important to understand for specialists working in all fields of knowledge related to designing and operation of devices and facilities for generation, conversion and transfer of energy. The mandatory assignments of the heat engineering course include three problems: – finding heat energy consumed by an ideal gas mixture, while it is being heated isochorically and isobarically, – calculating the thermodynamic parameters of states of an ideal gas during a cyclic process, as well as a work of the gas expansion, the thermal efficiency of the cycle, – calculating intensity of heat transfer in processes of forced and natural convection using criterial equations, solving the system of heat transfer and energy conservation equations. These methodological instructions contain tasks and methods of solving the assignments. Assignments solutions are expected to be given in handwritten form, done legible, and labeled with the student’s name, group and variant. Which variant of the task to solve is distributed by the lecturer. Calculated values must be presented with corresponding units of measurement permitted by International System of Units. The plots in solutions must be drawn keeping scale, their axes designated with titles, units and value labels near the tick marks. The works failing to meet said requirements are not accepted to be checked. After an assignment solution having been checked, the lecturer may ask additional theoretical questions related to the assignment topic to determine an appropriate mark. Self-check questions for preliminary making-ready for it are listed after the solving methods.
Keywords: methodological instructions; gas mixture heating; thermodynamic cycle; heat transfer